Vozmozhnosti optimizatsiya soderzhaniya mnogoletnei podgotovki sportivnogo rezerva v futbole - Zolotarev, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to discuss the opportunities of the young football-players' training improvement with a help of new approaches to optimization of their training process content. The next aspects of the long standing training of sports reserves in football are to be considered according the author's conception: 1) the young football-players competitive activities; 2) the quantitive parameters of the training loadings' specialization, orientation, coordinative complication and volume; 3) technical performance's improvement; 4) sensitive periods of development for coordinational capacities.